Preliminary experimental results of Sewage Sludge (SS) Co-digestion with Palm Oil Mill Effluent (POME) for Enhanced Biogas Production in Laboratory Scale Anaerobic Digester - Sivasankari R.; Kumaran P.; Normanbhay S.; Shamsuddin A.H. (Institute of Physics Publishing, 2023)
An investigation on the feasibility of co-digesting Sewage Sludge with Palm Oil Mill Effluent for enhancing the biogas production and the corresponding effect of the co-digestion substrate ratio on the biogas production has been evaluated. Anaerobic co-digestion of POME with SS was performed at ratios of 100:0, 70:30, 60:40 and 0:100 to find the optimum blend required for enhanced waste digestion and biogas production. Single stage batch digestion was carried out for 12 days in a laboratory scale anaerobic digester. Co-digestion of sludge's at the 70:30 proportion resulted in optimal COD and C: N ratio which subsequently recorded the highest performance with regards to biogas production at 28.1 L's compared to the 1.98 L's of biogas produced from digestion of SS alone. From the results obtained, it is evident that co-digestion of POME and SS is an attractive option to be explored for enhancement of biogas production in anaerobic digesters. Published under licence by IOP Publishing Ltd.